2023
DOI: 10.1177/16878132231175752
|View full text |Cite
|
Sign up to set email alerts
|

A review on preparation process and tribological performance of coatings for internal combustion engine piston ring

Abstract: Reducing the energy consumption and exhaust emission, and improving the combustion efficiency of internal combustion engine are important for solving the problems of climate change and environmental pollution. The piston ring-liner system is one of the most serious friction pairs in internal combustion engine, accounting for 26% of the total friction loss. Depositing strengthened coatings on the surface of piston rings is an effective method to reduce the friction coefficient and wear rate. This paper reviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…The results showed that CFD modeling approaches could be trusted and investigated the repercussions of diverse processes, both in detail and on a micro scale. Optimizing combustion is crucial for cutting down on fuel use and exhaust pollution [4]. More research on the consistency of these solutions inside the codes is required to allay concerns about the accuracy of findings, constraints, and dependability of codes.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that CFD modeling approaches could be trusted and investigated the repercussions of diverse processes, both in detail and on a micro scale. Optimizing combustion is crucial for cutting down on fuel use and exhaust pollution [4]. More research on the consistency of these solutions inside the codes is required to allay concerns about the accuracy of findings, constraints, and dependability of codes.…”
Section: Introductionmentioning
confidence: 99%
“…While electroplating coatings introduce pollution during the preparation process, thermal spray coatings tend to deform the piston ring during processing. Environmentally friendly physical vapor deposition (PVD) coatings exhibit superior performance, albeit with higher preparation costs [27]. Redesigning the end face structure to some extent also helps reduce piston ring temperatures, extending their lifespan and enhancing overall performance.…”
Section: Introductionmentioning
confidence: 99%